2020
DOI: 10.21203/rs.3.rs-61633/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Efficacy and Safety of Apatinib Treatment for Patients with Advanced or Recurrent Biliary Tract Cancer: A Retrospective Study

Abstract: Background The present study aims to evaluate the efficacy and safety of apatinib monotherapy or combination therapy for patients with advanced or recurrent biliary tract cancer(BTC). Methods Twenty-eight patients with advanced or recurrent BTC who progressed after prior systemic therapies and treated with apatinib from January 2017 to June 2019 were enrolled in this retrospective and observational study. The primary end point was progression free survival (PFS). Secondary end points included overall surviva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In a phase III trial of apatinib in patients with chemorefractory metastatic gastric cancer, the administration of apatinib 850 mg/day orally was associated with a high incidence of hematological and non-hematological adverse reactions, especially 19.9% of patients had bleeding, and 3.4% patients experienced a grade 3-4 AE of bleeding (10). In general, high-dose apatinib has been poorly tolerated; some clinical studies have revealed that low-dose apatinib is better tolerated (22,29). The dose of apatinib administrated in this study was 250 mg/day, which was much lower than the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase III trial of apatinib in patients with chemorefractory metastatic gastric cancer, the administration of apatinib 850 mg/day orally was associated with a high incidence of hematological and non-hematological adverse reactions, especially 19.9% of patients had bleeding, and 3.4% patients experienced a grade 3-4 AE of bleeding (10). In general, high-dose apatinib has been poorly tolerated; some clinical studies have revealed that low-dose apatinib is better tolerated (22,29). The dose of apatinib administrated in this study was 250 mg/day, which was much lower than the previous reports.…”
Section: Discussionmentioning
confidence: 99%